2017
DOI: 10.18632/oncotarget.17132
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-ketoglutarate (AKG) lowers body weight and affects intestinal innate immunity through influencing intestinal microbiota

Abstract: Alpha-ketoglutarate (AKG), a precursor of glutamate and a critical intermediate in the tricarboxylic acid cycle, shows beneficial effects on intestinal function. However, the influence of AKG on the intestinal innate immune system and intestinal microbiota is unknown. This study explores the effect of oral AKG administration in drinking water (10 g/L) on intestinal innate immunity and intestinal microbiota in a mouse model. Mouse water intake, feed intake and body weight were recorded throughout the entire exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
(49 reference statements)
2
31
0
Order By: Relevance
“…The serum AKG level was tested at 0, 1, 2, 4, and 6 h after gavage (n = 8 per group). ª 2020 The Authors The EMBO Journal 39: e103304 | 2020 (Chen et al, 2017). Moreover, we confirmed that acute oral administration resulted in increased circulating AKG (Fig 2A).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The serum AKG level was tested at 0, 1, 2, 4, and 6 h after gavage (n = 8 per group). ª 2020 The Authors The EMBO Journal 39: e103304 | 2020 (Chen et al, 2017). Moreover, we confirmed that acute oral administration resulted in increased circulating AKG (Fig 2A).…”
supporting
confidence: 73%
“…It has been shown that AKG lowered mouse body weight through influencing intestinal microbiota (Chen et al, 2017), suggesting another alternative mechanism for anti-obesity effects of AKG. On ▸ Figure 3.…”
mentioning
confidence: 99%
“…It is well known that treatment with antibiotics results in dysbiosis by decreasing diversity and taxonomic richness, shifting metabolic capacity, and reducing resistance to colonization . Conversely, our previous studies demonstrated that dietary AKG enhanced beneficial bacterial species and improved the composition of the intestinal microbiota in pig and mouse models . The mechanism might be that AKG served as a major energy source for intestinal microbiota and epithelial cells .…”
Section: Discussionmentioning
confidence: 80%
“…33 Conversely, our previous studies demonstrated that dietary AKG enhanced beneficial bacterial species and improved the composition of the intestinal microbiota in pig and mouse models. 34,35 The mechanism might be that AKG served as a major energy source for intestinal microbiota and epithelial cells. 27,35 Our previous report showed that dietary AKG improved energy metabolism in the small intestine of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…If AKG plays a physiological role in exercise-induced beneficial effects, AKG supplementation will mimic some of the metabolic effects of exercise. Water supplementation of AKG is well tolerated (Chen et al, 2017). Moreover, we confirmed that acute oral administration resulted in increased circulating AKG (Fig.…”
Section: Resultsmentioning
confidence: 99%